Access to Knowledge in India New Research on Intellectual Property, Innovation and Development - Subramanian, Ramesh; Shaver, Lea (Access to Knowledge, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. This is the third volume in our Access to Knowledge series. India is a $1 trillion economy which nevertheless struggles with a very high poverty rate and very low access to knowledge for almost seventy percent of its population which lives in rural areas. This volume features four parts on current issues facing intellectual property, development policy (especially rural development policy) and associated innovation, from the Indian perspective. Each chapter is authored by scholars taking an interdisciplinary approach and affiliated to Indian or American universities and Indian think-tanks. Each examines a policy area that significantly impacts access to knowledge. These include information and communications technology for development; the Indian digital divide; networking rural areas; copyright and comparative business models in music; free and open source software; patent reform and access to medicines; the role of the Indian government in promoting access to knowledge internationally and domestically.